Correction: Kommerein et al. Antiplanktonic and Antibiofilm Activity of Rheum palmatum Against Streptococcus oralis and Porphyromonas gingivalis. Microorganisms 2022, 10, 965 - Nadine Kommerein; Nina Vierengel; Jonathan Groß; Till Opatz; Bilal Al-Nawas; Lena Katharina Müller-Heupt (Microorganisms)
In the original publication [...]